Electrochemical treatment of real hospital wastewaters and monitoring of pharmaceutical residues by using surrogate models. Issue 5 (October 2019) - Ouarda, Yassine; Bouchard, Florence; Azaïs, Antonin; Vaudreuil, Marc-Antoine; Drogui, Patrick; Dayal Tyagi, Rajeshwhar; Sauvé, Sébastien; Buelna, Gerardo; Dubé, Rino
Graphical abstract: Highlights: Anodic oxidation was successfully applied for hospital wastewater treatment. An abatement rate of up to 100% of drug residues was obtained. UVA254 and TF are used as surrogate parameters and single correlations are proposed. Abstract: The electrochemical oxidation of drug residues in hospital wastewater has been studied. Treatment performances were evaluated by measuring the residual concentrations of twelve pharmaceutical compounds from different categories (caffeine, cihydrocarbamazepine, desvenlafaxine, sulfamethoxazole, venlafaxine, 2-hydroxy ibuprofen, carbamazepine, 4-hydroxy diclofenac, diclofenac, ibuprofen and clarithromycin). In order to follow the evolution of the treatment performances, high resolution mass spectrometry and spectral (UV-VIS and fluorescence) analysis were conducted and single correlations were proposed. Current densities were applied (4.42 mA.cm − ², 17.7 mA.cm − ² and 35.4 mA.cm − ²) for a period of 120 min using boron-doped diamond (NB/BDD) anode and titanium (Ti) cathode. Results showed that pollutants abatement rates in wastewater could reach 100% after 120 min at 35.4 mA.cm − ². The UV254 absorbance and total fluorescence (TF) were applied as surrogate parameters in order to monitor the degradation of the targeted contaminants in hospital wastewater. For each molecule, single correlation (0543 < R 2 < 0944) were proposed for on-line monitoring in future works.